2019
DOI: 10.1177/1747021819881265
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of utterance planning in response to pre-recorded and “live” utterances

Abstract: In everyday conversation, interlocutors often plan their utterances while listening to their conversational partners, thereby achieving short gaps between their turns. Important issues for current psycholinguistics are how interlocutors distribute their attention between listening and speech planning and how speech planning is timed relative to listening. Laboratory studies addressing these issues have used a variety of paradigms, some of which have involved using recorded speech to which participants responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 79 publications
(137 reference statements)
0
8
0
Order By: Relevance
“…Our study was not specifically designed to test the effect of cognitive load on perceptual learning. However, other researchers have found that speaking with a physically co-present interlocutor involves a higher cognitive processing load than speaking in response to prerecorded utterances (Sjerps et al, 2020). Thus, our experiment's face-to-face setting might well have induced a higher processing load than the computer player setting, yet still it led to equivalent perceptual learning.…”
Section: The Interactive Context For L2 Sound Learningmentioning
confidence: 58%
“…Our study was not specifically designed to test the effect of cognitive load on perceptual learning. However, other researchers have found that speaking with a physically co-present interlocutor involves a higher cognitive processing load than speaking in response to prerecorded utterances (Sjerps et al, 2020). Thus, our experiment's face-to-face setting might well have induced a higher processing load than the computer player setting, yet still it led to equivalent perceptual learning.…”
Section: The Interactive Context For L2 Sound Learningmentioning
confidence: 58%
“…Nevertheless, given their high frequency, at least some function words may be faster to plan than content words. This is important because in earlier work, gap durations in conversation have often been compared to speech production latencies for nouns, specifically picture names (e.g., Garrod and Pickering, 2015;Levinson and Torreira, 2015;Barthel et al, 2016;Bögels et al, 2018;Barthel and Sauppe, 2019;Sjerps et al, 2020), and relative to these latencies gaps in conversation are very short. This comparison may be misleading as it ignores the difference in word class and any related differences in the speech planning processes.…”
Section: Discussionmentioning
confidence: 99%
“…(late cue) versus "Are dogs your favorite animals?" (early cue); see also Corps et al, 2019], and in several studies where participants and confederates took turns describing objects on their screens (e.g., Sjerps and Meyer, 2015;Barthel et al, 2016;Meyer et al, 2018;Sjerps et al, 2020). All of these studies found faster responses when the cue to the answer appeared early rather than late in the question, indicating that, when possible, participants began to plan the answer during the question.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…We designed a baseline task that is typical for the type of segmentation projects that are conducted for production data in psycholinguistics (for instance, Zormpa et al 2019;Sjerps et al 2019), combining forced-alignment and Praat TextGrid annotation.…”
Section: Baseline Manual Segmentation Methodsmentioning
confidence: 99%